Autoantibodies to Annexin A2 and cerebral thrombosis: Insights from a mouse model - Weiss, Ronen (Lupus, 2021)
INTRODUCTION: Antiphospholipid syndrome (APS) is an autoimmune disorder manifested by thromboembolic events, recurrent spontaneous abortions and elevated titers of circulating antiphospholipid antibodies. In addition, the presence of antiphospholipid antibodies seems to confer a fivefold higher risk for stroke or transient ischemic attack. Although the major antigen of APS is β(2) glycoprotein I, it is now well established that antiphospholipid antibodies are heterogeneous and bind to various targets. Recently, antibodies to Annexin A2 (ANXA2) have been reported in APS. This is of special interest since data indicated ANXA2 as a key player in fibrinolysis. Therefore, in the present study we assessed whether anti-ANXA2 antibodies play a pathological role in thrombosis associated disease. MATERIALS AND METHODS: Mice were induced to produce anti-ANXA2 antibodies by immunization with ANXA2 (iANXA2) and control mice were immunized with adjuvant only. A middle cerebral artery occlusion stroke model was applied to the mice. The outcome of stroke severity was assessed and compared between the two groups. RESULTS: Our results indicate that antibodies to ANXA2 lead to a more severe stroke as demonstrated by a significant larger stroke infarct volume (iANXA2 133.9 ± 3.3 mm(3) and control 113.7 ± 7.4 mm(3); p = 0.017) and a more severe neurological outcome (iANXA2 2.2 ± 0.2, and control 1.5 ± 0.18; p = 0.03). CONCLUSIONS: This study supports the hypothesis that auto-antibodies to ANXA2 are an independent risk factor for cerebral thrombosis. Consequently, we propose screening for anti-ANXA2 antibodies should be more widely used and patients that exhibit the manifestations of APS should be closely monitored by physicians.